Women's status, fertility decline and women's health in developing countries: direct and indirect influences of social status on health - Wickrama, K.A.S. (2002)
In the present three-wave study of 72 developing countries, we use growth curves to examine how changes in fertility and level of fertility mediate the effect of women's social status on women's health as measured by infant mortality, maternal mortality, and female life expectancy. We find that level of female education, average age at marriage, and the percentage of married women using contraceptives influence attained level of fertility, with controls for economic growth and dependency status. Change in fertility, however, is predicted only by average age at marriage and by level of education. Change in fertility, in turn, predicts improvement in all three women's health indicators, while the level of fertility predicts improvement in maternal mortality and infant mortality. In addition to the mediating effects of fertility, both age at marriage and education contribute directly to reduced level of infant mortality; level of primary education contributes directly to improvement in female life expectancy. These findings provide strong evidence that women's social status makes direct contributions to women's health which cannot be attributed to economic growth, dependency status, and/or the mediating effects of level and change in fertility. The policy implication for developing countries is that greater gains can be made in women's health, particularly maternal health, by improving women's social status, especially in rural areas. - Reproduced.
Keywords: Social status - Developing Countries; Fertility - Developing Countries; Womens status - Developing Countries; Womens status